2017
DOI: 10.1097/qad.0000000000001575
|View full text |Cite
|
Sign up to set email alerts
|

Potential for immune-driven viral polymorphisms to compromise antiretroviral-based preexposure prophylaxis for prevention of HIV-1 infection

Abstract: Results illustrate the potential for a natural immune-driven HIV-1 polymorphism to compromise antiretroviral-based prevention, particularly in key epidemic regions. Regional reverse transcriptase-E138X surveillance should be undertaken before use of rilpivirine PrEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In a study, 7772 antiretroviral‐naïve patients were recruited to analyse linked reverse transcriptase‐E138X/HLA data. The results show that HLA‐B18 and all HIV‐1 subtypes except subtype A are strongly correlated with reverse transcriptase‐E138X variants in RPV resistance and that the antiretroviral PrEP can be compromised by natural immune‐driven HIV‐1 polymorphism . In KwaZulu‐Natal, South Africa, RPV PrEP is cost‐effective, and the drug resistance of PrEP was less when compared to ART …”
Section: Non‐nucleoside Reverse Transcriptase Inhibitormentioning
confidence: 97%
“…In a study, 7772 antiretroviral‐naïve patients were recruited to analyse linked reverse transcriptase‐E138X/HLA data. The results show that HLA‐B18 and all HIV‐1 subtypes except subtype A are strongly correlated with reverse transcriptase‐E138X variants in RPV resistance and that the antiretroviral PrEP can be compromised by natural immune‐driven HIV‐1 polymorphism . In KwaZulu‐Natal, South Africa, RPV PrEP is cost‐effective, and the drug resistance of PrEP was less when compared to ART …”
Section: Non‐nucleoside Reverse Transcriptase Inhibitormentioning
confidence: 97%
“…This is supported by the fact that E138K_RT mutation is associated with faster CD4 T cell decline by the Kaplan-Meier analysis (p = 0.002) (Figure 2). As E138K_RT is a well-known escape mutation [30], it suggests that the HLA class I restricted CD8 CTL responses that drove E138K to escape mutation. Indeed, the E138K_RT is significantly associated with several high-frequency HLA class I genotypes such as A*68:02 (17.99%), B*45:01(11%), and A*66:01(7.5%).…”
Section: Discussionmentioning
confidence: 99%
“…We observed such ex in our study. For example, E138K, a well-known escape mutation [30], was first ide in participant ML874 (A*68:02+) in the blood sample collected in 1996, and this DR also detected in the samples collected in 2003 from the same participant. Moreover, was identified first in participant ML264 (A*68:02+), and in samples collected in 19 DRM was also present in two samples collected from the same patient more than 7.5 years later in 2003.…”
Section: Pre-art Drug Resistance Associated With Hla Class I Allelesmentioning
confidence: 99%
“…RT-I135T/V/L (selected by B*51 and B*52 [39]) and RT-283I/L (selected by B*15 [39]) confer up to 3-fold reduced in vitro susceptibility to first-generation Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTIs) [116], while RT-E138G/A/K, selected by B*18 [29,117] can mediate up to 7-fold decreased susceptibility to the second-generation NNRTI rilpivirine [117]. The latter was recently highlighted as an example of a natural immune-driven viral polymorphism that could compromise antiretroviral-based HIV prevention [118], otherwise known as Pre-exposure prophylaxis (PrEP). Rilpivirine was initially favored as a potential PrEP agent as it was available in a long-acting form [119].…”
Section: How Else May Hiv Adaptation To Hla Influence Hiv Prevention Strategies?mentioning
confidence: 99%
“…Rilpivirine was initially favored as a potential PrEP agent as it was available in a long-acting form [119]. However, analysis of linked viral/HLA genotypes from nearly 8000 antiretroviral-naive individuals confirmed that RT-E138G/A/K prevalence varied markedly across the globe, with frequencies exceeding 10% in key epidemic regions (including Sub-Saharan Africa and Eastern Europe) where HLA-B*18 carriage was common [118]. These results underscored the potential for HIV adaptation to HLA to compromise PrEP efficacy in the very regions that need it most, leading researchers to recommend regional HIV polymorphism surveillance prior to PrEP rollout and call for enhanced collaboration across the immune and drug resistance fields.…”
Section: How Else May Hiv Adaptation To Hla Influence Hiv Prevention Strategies?mentioning
confidence: 99%